PSCA is a target of chimeric antigen receptor T cells in gastric cancer - Di Wu; Jiang Lv; Ruocong Zhao; Zhiping Wu; Diwei Zheng; Jingxuan Shi; Simiao Lin; Suna Wang; Qiting Wu; Youguo Long; Peng Li; Yao Yao (Biomarker Research, 2020)
Abstract Background Gastric cancer is a deadly malignancy and is a prognostically unfavorable entity with restricted therapeutic strategies available. Prostate stem cell antigen (PSCA) is a glycosylphosphatidylinositol (GPI)-anchored cell surface protein widely expressed in bladder, prostate, and pancreatic cancers. Existing studies have thoroughly recognized the availability of utilizing anti-PSCA CAR-T cells in the treatment of metastatic prostate cancer and non-small-cell lung cancer. However, no previous study has investigated the feasibility of using anti-PSCA CAR-T cells to treat gastric cancer, irrespective of the proven expression of PSCA on the gastric cancer cell surface. Methods We determined the expression of PSCA in several primary tumor tissues and constructed third-generation anti-PSCA CAR-T cells. We then incubated anti-PSCA CAR-T cells and GFP-T cells with target tumor cell lines at E:T ratios of 2:1, 1:1, 1:2, and 1:4 to evaluate the therapeutic efficacy of anti-PSCA CAR-T cells in vitro. We also assayed canonical T cell activation markers after coculturing anti-PSCA CAR-T cells with target cell lines by flow cytometry. The detection of a functional cytokine profile was carried out via enzyme-linked immunosorbent assays. We then evaluated the antitumor activity of anti-PSCA CAR-T cells in vivo by establishing two different xenograft GC mouse models. Results Anti-PSCA CAR-T cells exhibited upregulated activation markers and increased cytokine production profiles related to T cell cytotoxicity in an antigen-dependent manner. Moreover, anti-PSCA CAR-T cells exhibited robust anti-tumor cytotoxicity in vitro. Importantly, we demonstrated that anti-PSCA CAR-T cells delivered by peritumoral injection successfully stunted tumor progression in vivo. However, intravenous administration of anti-PSCA CAR-T cells failed to reveal any therapeutic improvements. Conclusions Our findings corroborated the feasibility of anti-PSCA CAR-T cells and their efficacy against gastric cancer, implicating the potential of applying anti-PSCA CAR-T cells to treat GC patients in the clinic.